The Analysis of Public Green Open Space Management in Jambi City - Irsadunas Noveri; Khairun Najib; M. Yusuf (Policy & Governance Review, 2020)
The growth of the population requires space to accommodate human activities. The development aims to provide a space for humans, but it has an impact on the decreasing green open space. The majority of previous research examines the policy, policy implementation, community support/ involvement, and the need for green open space. While this study examines the management and the factors of the management of public green open space, the research uses a descriptive qualitative method by utilizing primary data through interviews and observations and is supported by secondary data, such as reports, rules, and research results. This study found that the management of green open space, and regulations were available at the regional level; however, for the fulfilment of public green open space only reached 10.76% while still lacking 9.24% because the management faces the substance and technical problems. To fix these deficiencies requires a master plan and a strong leadership commitment to realize these deficiencies.